Analysis from the view of risk between employer and employees at Espek Risda Keratong, Rompin Pahang / Kamaruzaman Karim - Karim, Kamaruzaman (Faculty of Plantation and Agrotechnology, 2016)
The study is indicating the view of risks between employer and employees in oil palm sector which influenced the highest risk level due to several types of risk. The type of risks contribute to the high accident rates usually influencing are physical, biological, psychosocial and chemical. A simple random technique was used to selected sample of 80 workers which represent 19 employer and 61 employees at one of the estates in ESPEK Risda Keratong, Rompin. The questionnaire was done to the selected respondent. Descriptive, Regression and Independent t-test sample analysis are used in this research to analyze the data by using SPSS software. From the analyzing process the relationship between independent and dependent were found. Based on the result, researching found physical, biological and chemical factor have significant relationship toward the rate of accident among worker while psychosocial has not significant relationship toward the rate of accident among employer and employees.